Developing an Intervention for Suicide Prevention: A Rapid Review of Lived Experience Involvement. Issue 2 (3rd April 2022) - Watling, David; Preece, Megan; Hawgood, Jacinta; Bloomfield, Sharyn; Kõlves, Kairi
Abstract: Objective: While suicide prevention interventions should be informed by lived experience, there are no reviews examining involvement of lived experience (LE) thus far. This rapid review aimed to synthesize available studies using LE of suicidality to guide the development of suicide prevention interventions. Method: A rapid review following PRISMA guidelines was conducted. Key electronic databases were searched for the literature for the last 10 years (2010 until June 2019) to identify studies that have incorporated the lived experience of people of suicide to develop a suicide prevention intervention. Key features of the LE intervention development process were synthesized and discussed. Results: A final 11 studies from 13 papers were selected for synthesis. Most studies employed focus groups (73%). Research questions focused on participant preferences, experiences, and recommendations for suicide prevention interventions. Considering the qualitative nature, majority of studies used thematic analyses to study participant responses and generate intervention components based on identified themes. Translation from research findings into a physical intervention was described in limited detail across all studies. The rapid review was limited to the literature about development of interventions using LE of suicide published in English in last 10 years. Conclusions: With an increased focus on person-centered care and LE in suicide prevention, such valuable expertise should be integrated into intervention development. This review provides insight into the process to ensure responses to suicidal persons are well aligned with the needs of those they serve. Highlights: Limited studies have involved lived experience in the development of interventions Focus groups and thematic analysis are common methods to develop interventions Limited description of translating themes into intervention components is described